Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/cancers14081946
|View full text |Cite
|
Sign up to set email alerts
|

Elevating SOX2 Downregulates MYC through a SOX2:MYC Signaling Axis and Induces a Slowly Cycling Proliferative State in Human Tumor Cells

Abstract: Slowly cycling/infrequently proliferating tumor cells present a clinical challenge due to their ability to evade treatment. Previous studies established that high levels of SOX2 in both fetal and tumor cells restrict cell proliferation and induce a slowly cycling state. However, the mechanisms through which elevated SOX2 levels inhibit tumor cell proliferation have not been identified. To identify common mechanisms through which SOX2 elevation restricts tumor cell proliferation, we initially performed RNA-seq … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Mouse remains the only species for which generation of all-iPSCs animals has been reported 122124 ; and germline competence has been reported only for mouse and male rat 125 , highlighting the limitations of today’s technologies. Naïve PSCs have lower Myc levels compared to primed cells 97,99 , which could be a direct effect of high levels of Sox2 126 in naïve cells (Fig. 6e).…”
Section: Discussionmentioning
confidence: 99%
“…Mouse remains the only species for which generation of all-iPSCs animals has been reported 122124 ; and germline competence has been reported only for mouse and male rat 125 , highlighting the limitations of today’s technologies. Naïve PSCs have lower Myc levels compared to primed cells 97,99 , which could be a direct effect of high levels of Sox2 126 in naïve cells (Fig. 6e).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, CML LSCs are highly sensitive to alterations in c-Myc expression, which is required for the maintenance of CML leukemia-initiating cells [ 57 , 58 ]. Although the relationship between c-Myc and SOX2 in cancer cells remains unclear, some studies suggest that they co-localize within a protein complex [ 59 , 60 ]. Specifically, c-Myc has been shown to regulate the expression of the SOX2 gene in breast cancer-derived CSCs [ 61 ], implying that c-Myc may modulate the expression of other transcription markers to regulate cancer stemness.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] Considering about 20% of mice offspring derived from iPSCs were found to develop tumors, it was questioned that the attributes of so-called stem cell is more like those of tumor cells and MYC, KLF4 genes might be carcinogenic. [21] Even though more and more studies indicated that the stem cell transcription factors play important roles in maintaining the self-renewal, reprogramming and multiple differentiations of tumor cells, [22,23] how OSKM genes participate in these processes still needs to be further explored.…”
Section: Introductionmentioning
confidence: 99%